Approach to Posture and Gait in Huntington’s Disease - Talman, Lauren S.; Hiller, Amie L. (Frontiers in Bioengineering and Biotechnology, 2021)
Disturbances of gait occur in all stages of Huntington’s disease (HD) including the premanifest and prodromal stages. Individuals with HD demonstrate the slower speed of gait, shorter stride length, and increased variability of gait parameters as compared to controls; cognitive disturbances in HD often compound these differences. Abnormalities of gait and recurrent falls lead to decreased quality of life for individuals with HD throughout the disease. This scoping review aims to outline the cross-disciplinary approach to gait evaluation in HD and will highlight the utility of objective measures in defining gait abnormalities in this patient population.